Analisis Kinerja Keuangan Perusahaan Sektor Consumer Cyclicals dan Sektor Transportation & Logistic sebelum dan saat Pandemi Covid-19 - Andriana, Dita; Septriani, Yossi; Ferdawati, Ferdawati (Media Bisnis, 2023)
The COVID-19 pandemic has had a significant impact on the business activities of all industrial sectors in Indonesia. One of the sectors affected is the transportation & logistics sector, which experienced a 30% decrease in turnover compared to before the pandemic, as well as the consumer cyclicals sector. This study analyzes the financial performance of consumer cyclicals sector and transportation & logistics sector before and during the pandemic in 2018-2021. The sampling technique used was purposive sampling. The data analysis methods used are paired sample t-test and Wilcoxon signed rank test, which previously carried out a normality test. The results of this study indicate that for the consumer cyclical sector, financial performance as measured by current ratio, quick ratio, debt to asset ratio, and debt to equity ratio does not have a significant difference between before and during the COVID-19 pandemic, while net profit margin, return on assets, total asset turnover and working capital turnover have a significant difference between before and during the pandemic. For companies engaged in the transportation & logistics sector, debt to equity ratio and working capital turnover do not have significant differences between before and during the pandemic, while the current ratio, quick ratio, net profit margin, return on assets, debt to asset ratio, and total asset turnover have significant differences between before and during the covid-19 pandemic. The findings conclude that the transportation & logistics sector experienced higher changes in liquidity-related financial performance compared to the consumer cyclicals sector, while the consumer cyclicals sector experienced significant changes in profit performance before and during the pandemic.